Allopurinol is an independent determinant of improved arterial stiffness in chronic kidney disease: a cross-sectional study. - Khai P Ng; Stephanie J Stringer; Mark D Jesky; Punit Yadav; Rajbir Athwal; Mary Dutton; Charles J Ferro; Paul Cockwell (PLoS ONE)
Background Arterial stiffness is increased in patients with CKD and is a powerful predictor of cardiovascular morbidity and mortality. Use of the xanthine oxidase inhibitor allopurinol has been shown to improve endothelial function, reduce left ventricular hypertrophy and possibly improve cardiovascular outcome. We explored the relationship between use of allopurinol and arterial stiffness in patients with chronic kidney disease (CKD). Methods Cross-sectional observational study of 422 patients with CKD with evidence of, or at high risk of, renal disease progression. Arterial stiffness was determined by carotid-femoral pulse wave velocity (PWV). Results The mean age was 63 ± 16 years, median estimated glomerular filtration rate was 25 (interquartile range: 19-31) ml/min/1.73 m(2) and mean PWV was 10.2 ± 2.4 m/s. Seventy-seven patients (18%) were receiving regular allopurinol, 61% at a dose of 100 mg/day (range: 50-400 mg/day). Patients receiving allopurinol had significantly lower peripheral pulse pressure, central pulse pressure, central systolic blood pressure, serum uric acid level tissue advanced glycation end product levels but comparable high-sensitivity C-reactive protein levels. Use of allopurinol was associated with lower PWV. After adjusting for age, gender, ethnicity, tissue advanced glycation end product level, peripheral pulse pressure, smoking pack years, presence of diabetes mellitus and use of angiotensin converting enzyme inhibitor or angiotensin II receptor blocker, the use of allopurinol remained a significant independent determinant of PWV (mean difference: -0.63 m/s; 95% CI, -0.09 to -1.17 m/s, p = 0.02). Conclusion In patients with CKD, use of allopurinol is independently associated with lower arterial stiffness. This study provides further justification for a large definitive randomised controlled trial examining the therapeutic potential of allopurinol to reduce cardiovascular risk in people with CKD.